AbobotulinumtoxinA provides flexibility for the treatment of cervical dystonia with 500 U/1 mL and 500 U/2 mL dilutions. (2021) - Lew, Mark F.; Hauser, Robert A.; Isaacson, Stuart H.; Truong, Daniel; Patel, Atul T.; Brashear, Allison; Ondo, William; Maisonobe, Pascal; Dashtipour, Khashayar; Bahroo, Laxman; Wietek, Stefan
Highlights: Cervical dystonia has significant impact on quality of life of those affected. Dilution options allow for treatment flexibility and individualized patient care. AboBoNT-A is efficacious with similar safety and tolerability at either dilution. Abstract: Introduction: Cervical dystonia (CD) is a neurologic movement disorder with potentially disabling effects and significant impact on quality of life of those affected. AbobotulinumtoxinA (aboBoNT-A) was initially approved for a dilution of 500 U/1 mL and subsequently for a dilution of 500 U/2 mL, providing flexibility for clinicians to treat CD. Here, we explore the safety and efficacy of the 500 U/2 mL dilution versus 500 U/1 mL dilution of aboBoNT-A in a retrospective analysis based on published clinical trial data. Methods: The safety and efficacy of aboBoNT-A in patients with CD was evaluated in three multicenter, double-blind, randomized, placebo-controlled trials and open-label extensions. Trials 1 (NCT00257660) and 2 (NCT00288509) evaluated the 500 U/1 mL dilution in 80 and 116 patients, respectively; Trial 3 (NCT01753310) evaluated the 500 U/2 mL dilution in 125 patients. Results: Comparison of the adjusted mean difference in TWSTRS total scores at Week 4 from baseline for aboBoNT-A in Trial 1 (−6.0; 95% CI, −10.8, −1.3), Trial 2 (−8.8; 95% CI, −12.9, −4.7), and Trial 3 (−8.7; 95% CI, −13.2, −4.2) showed similar, significant improvements. Dysphagia and muscle weakness patterns were comparable across the three trials, indicating that an increased dilution of aboBoNT-A does not result in an increased risk of diffusion-related adverse events. Conclusion: The results of these trials show that aboBoNT-A is similarly efficacious using either dilution, with similar safety and tolerability across trials. Having the 500 U/1 mL and 500 U/2 mL dilution volumes available provides further flexibility in administration, benefiting patient care.